KESULITAN BELAJAR SISWA FASE C SD PADA MATERI PEMBAGIAN DALAM MATA PELAJARAN MATEMATIKA SD - Desri Estiana Faot; Anastassya Norita Grasella Bua; Anita Fallo; Angelica Devara Modok; Jarismon Salomo Kamlasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the difficulties students encounter in completing division operations and the factors that cause these difficulties among fifth-grade students in Class V-A at an elementary school in Kupang City. Using a qualitative descriptive approach, this study involved 22 students and their teacher as data sources. Data were collected through observation, tests, interviews, and documentation studies, then analysed to identify patterns of errors and obstacles experienced by students. The results showed that students experienced three main types of difficulties, namely division with remainders, long division, and solving word problems. These difficulties were mainly caused by weak mastery of multiplication, inaccuracy in subtraction steps, and an inability to systematically organise the work process. In addition to internal factors such as a low understanding of basic concepts, external factors such as a lack of learning support from families and low learning motivation were also found. Teachers' efforts to overcome these difficulties included reinforcing basic concepts, repeated practice, and the use of learning media, although the use of concrete teaching aids was still limited. Therefore, improving division skills requires strengthening basic numerical concepts, continuous concrete learning, and parental involvement in supporting the students' learning process.